2021
DOI: 10.3390/healthcare9070839
|View full text |Cite
|
Sign up to set email alerts
|

A User-Driven Approach to Prosthetic Upper Limb Development in Korea

Abstract: Despite recent significant advances in technology and medicine, the number of patients who undergo amputation of body parts for various reasons continues to increase. Assistive devices such as prosthetic arms can enable limited activities in upper limb amputees and improve their quality of life. This study aims to help in the development of user-centered prosthetics by identifying user requirements and key considerations during selection of prosthetics. This study conducted a questionnaire survey after obtaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…16 Furthermore, those who have lost their hand face significant limitations when performing daily tasks. 32 In this regard, those who wear upper-limb prostheses should learn precise ways for controlling their devices and performing daily movements independently.…”
Section: Resultsmentioning
confidence: 99%
“…16 Furthermore, those who have lost their hand face significant limitations when performing daily tasks. 32 In this regard, those who wear upper-limb prostheses should learn precise ways for controlling their devices and performing daily movements independently.…”
Section: Resultsmentioning
confidence: 99%
“…Already in 2021, we found a large number of publications, as in 2020, specifically, 28 publications that related golf and health [ 32 , 33 , 34 , 35 , 36 , 71 , 72 , 73 , 74 , 99 , 100 , 101 , 102 , 103 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 ], 6 of them in both databases [ 71 , 73 , 100 , 102 , 185 , 190 ]. The main line of research continues to be the health benefits of sport [ 38 , 39 , 40 , 41 , 42 ] and studies on injuries [ 145 , 146 , 177 , 178 , 179 ] or risks to players on the golf course [ 183 , 187 ].…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, participatory action research allows a shift from thinking of people as "end-users" towards integrating them as equal members of the team developing the technology (i.e., making technology with people instead of for them), ensuring development from idea generation to implementation is relevant to their lived experiences (7). Several studies have reported the perspectives of prosthesis users in the context of current clinically available prosthetic technology, such as cosmesis (making the prosthesis aesthetically pleasing), prosthetic fit/ comfort, functionality, and specific prosthetic componentry that may help clinicians provide the best services for their patients (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). However, there is limited research focusing on user perspectives regarding future technology to guide the development of new prosthetic devices (22)(23)(24)(25).…”
Section: Utilize User-centered Design and Participatory Action Researchmentioning
confidence: 99%